PERANAN SUMBERDAYA HUTAN DALAM PEREKONOMIAN DAN DAMPAK PEMUNGUTAN RENTE HUTAN TERHADAP KELESTARIAN HUTAN DI KABUPATEN GOWA - Syamsu Alam; . Hajawa (PERENNIAL, 2007)
Kabupaten Gowa has 63.099 ha forest area, consists of 24.226 ha of protected forest, 3.309 ha of conservation forest/recreation forest, and 35.554 ha of production forest. The value of forest resource can be estimated based on use value an non use value. Use value of forest resource in Kabupaten Goewa covers direct economic value wich is obtained from timber product and non timber product. While indirect economic value is obtained from iriigation water, fresh water, agriculture production increase, and forest recreation value and also contribution in labour section. Contribution of agricultural sector in Bruto Regional Domestic Product (Produk Domestik Regional Bruto = PDRB) of Kabupaten Gowa base on the data of 2000 to 2005 is high enough, more than half of PDRB of Kabupaten Gowa which is 52,29 %. However the contribution of subsector of forestry to the economy of Kabupaten Gowa is very small, only 0,17 %. the use of ecpnomy rent for land of rehabilitation in 2005 has been use as much as Rp. 142.384.858,- for 95,50 ha of area. This fund is come from Dana Alokasi Khusus - Dana Reboisasai(DAK-DR)40 % (special allocation fund-reforestration fund 40 %) the part is managed by the region of production. Keywords: Forest rent, forest sustainability References